2021
DOI: 10.1111/ijcs.12767
|View full text |Cite
|
Sign up to set email alerts
|

Consumer e‐waste disposal behaviour: A systematic review and research agenda

Abstract: E‐waste is the world's fastest‐growing waste stream, and it contains toxic chemicals that are harmful to human health. Research has shown that the vast majority of consumers are unwilling to dispose of e‐waste, preferring to keep obsolete products at home rather than returning them to manufacturers for recycling. Despite the evident importance of this area of research, there is yet to be a systematic assessment of e‐waste disposal behaviour that summarises the relationships among constructs in the forms of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 156 publications
0
18
0
Order By: Relevance
“…When different approaches were examined the current review can be defined most similar to Paul et al.’s (2021) scientific procedures and rationels for systematic reviews (SPAR‐4‐SLR) method. Similar to previous research (e.g., Gilal et al., 2021), we applied certain steps starting with the identification of sources (journals), acquisition of relevant articles from the WOS database, purification of articles (application of exclusion and inclusion criteria to raw data), analysis and evaluation of articles, and reporting findings. The following section provides in‐depth information on data retrieval and processing.…”
Section: Methodsmentioning
confidence: 99%
“…When different approaches were examined the current review can be defined most similar to Paul et al.’s (2021) scientific procedures and rationels for systematic reviews (SPAR‐4‐SLR) method. Similar to previous research (e.g., Gilal et al., 2021), we applied certain steps starting with the identification of sources (journals), acquisition of relevant articles from the WOS database, purification of articles (application of exclusion and inclusion criteria to raw data), analysis and evaluation of articles, and reporting findings. The following section provides in‐depth information on data retrieval and processing.…”
Section: Methodsmentioning
confidence: 99%
“…Another group of articles related to the previous category (it could be a sub‐category of environmental‐related issues) is Consumer Social Responsibility , which includes four articles. The articles map socially responsible consumption (Falcão & Roseira, 2022), identify determinants of consumer green innovation behavior (Flores & Jansson, 2022), e‐waste consumer behavior (Gilal et al, 2022), and sustainable fashion (Busalim et al, 2022). The third category includes four articles on the Digital World and New technologies .…”
Section: Aligning Reviews Of Literature With the Aims And Scope Of Th...mentioning
confidence: 99%
“…According to research, the great majority of customers refuse to dispose of e‐waste, preferring to retain outmoded items at home rather than sending them to manufacturers for recycling. In the article titled, “ Consumer e‐waste disposal behavior: A systematic review ” by Gilal et al (2022) provide a synthesis of prior research in this area of inquiry and explain how their review will serve as a base to guide future research focusing on this topic. The purpose of their article is to promote e‐waste disposal behavior by looking at how such behavior has been utilized as a construct in the literature and what theories, contexts, characteristics, and methodological approaches have been used to strengthen this behavior.…”
Section: Aligning Reviews Of Literature With the Aims And Scope Of Th...mentioning
confidence: 99%
“…Nevertheless, an extensive SLR by Gilal et al (2021) suggested the dearth of comprehensive studies on ewaste awareness and disposal behavior in developing nations, mainly in South Asia. Besides, the researchers conducted all of these studies on the general public, which entirely overlooked the speci ed responses from the actual consumers such as students, industry personnel, and managers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, none of these studies focused on consumer awareness about e-waste and its disposal practices. Besides, a recent systematic literature review (SLR) by Gilal et al (2021) highlighted the absence of comprehensive studies on consumers' awareness of e-waste and its disposal practices in developing nations, mainly in South Asia. Further, researchers conducted these scholarships on the mass level/ general public, which overlooked the speci ed responses from the actual consumers such as students, industry personnel, and managers.…”
Section: Introductionmentioning
confidence: 99%